2018
DOI: 10.1051/ocl/2018056
|View full text |Cite
|
Sign up to set email alerts
|

The PeaMUST project: defining ideotypes for the pea crop development

Abstract: Pea is the most widely cultivated grain legume crop in Europe. In the French research project PeaMUST, a large public and private sector partnership has been set up to undertake complementary strategies towards the development of high and stable yielding cultivars. These different strategies will contribute to the definition of a pea ideotype based on both a priori and a posteriori approaches. On the one hand, genomic selection will identify interesting genotypes which may display new phenotypic ideotypes. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…The largest difference between the two leaf types is in lodging (Table 3); the normal‐leafed group was seriously lodging right after flowering and during pod filling. Normal‐leafed peas had, on average, a higher plant length than semi‐leafless cultivars, because many of the more recent semi‐leafless cultivars carry the semi‐dwarf mutant (Burstin et al., 2018). However, due to lodging, normal‐leafed peas had a lower plot height.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest difference between the two leaf types is in lodging (Table 3); the normal‐leafed group was seriously lodging right after flowering and during pod filling. Normal‐leafed peas had, on average, a higher plant length than semi‐leafless cultivars, because many of the more recent semi‐leafless cultivars carry the semi‐dwarf mutant (Burstin et al., 2018). However, due to lodging, normal‐leafed peas had a lower plot height.…”
Section: Discussionmentioning
confidence: 99%
“…Pea seeds are rich in protein (Atta et al., 2004). Because of the symbiosis with atmospheric‐N fixing rhizobacteria, peas do not require N fertilizer and sometimes they contribute N to the following crop (Burstin et al., 2018). Therefore, peas are of particular interest in organic crop rotations (Gollner et al., 2019), but they can also contribute to crop diversity and energy efficiency in conventional production (Nemecek et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ideotypes for pea under different conditions have previously been investigated. In the French PeaMUST project, the focus was on plant architecture and resistance traits to avoid stress (Burstin et al, 2018 ). Annicchiarico and Filippi ( 2007 ) identified traits suitable for organic production in Northern Italy, such as weed competition, while Castel et al ( 2017 ) investigated the winter hardiness traits important in French winter peas in response to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the genetic improvement in pea crops has been achieved through the manipulation and use of the afila mutation, which is expressed in homozygous recessive condition ( afaf ), with the transformation of leaves into tendrils. It can generally be concluded that the stronger the tendril growth, the greater the resistance to lodging (Burstin et al., 2018; Reid & Ross, 2011; Wang et al., 2003).…”
Section: Introductionmentioning
confidence: 99%